Students’ Experiences of Working With a Socio-Scientific Issues-Based Curriculum Unit Using Role-Playing to Negotiate Antibiotic Resistance - Sagmeister, Konstantin J.; Schinagl, Christoph W.; Kapelari, Suzanne; Vrabl, Pamela (Frontiers in Microbiology, 2021)
The emergence and widespread of antibiotic-resistant pathogenic microorganisms are of great individual and societal relevance. Due to the complex and multilayered nature of the topic, antibiotic resistance (ABR) is the object of concern for several scientific fields such as microbiology or medicine and encompasses a broad range of political, economic, and social aspects. Thus, the issue related to antibiotic-resistant bacterial diseases offers an excellent platform for designing and implementing the teaching and learning of socio-scientific issues (SSI). We created a SSI-based curriculum unit for use in secondary science classrooms by developing a collaborative partnership between education researchers and microbiologists. This classroom environment allows students to explore and negotiate ABR as a societal and scientific phenomenon. For this purpose, we leveraged role-playing within the SSI-based unit as a productive context for engaging students in learning opportunities that provide multiple perspectives on ABR and the complex interplay of its accelerators. This case-based paper describes Austrian school students’ experiences from their participation in a SSI-embedded role-playing classroom environment and subsequent activities that included a mini congress with a poster presentation and a panel discussion. An open-ended questionnaire-based assessment tool was used to examine the situational characteristics of the students’ work. To assess students’ contributions, we applied a qualitative content analysis design and identified cognitive and affective outcomes. The students’ learning experiences demonstrate that they considered the content—the social complexities of antibiotic-resistant bacteria and associated diseases—exciting and very topical. The students perceived that learning about ABR is relevant for their future and involves both individual and societal responsibility for action. Although the curriculum unit and its assignments were described as labor-intensive, it became apparent that the role-playing setting has the potential to inform students about multiple stakeholder positions concerning ABR. Concerning the promotion of science practices, almost all students claimed that they learned to organize, analyze, evaluate, and present relevant information. Moreover, the students affirmed that they learned to argue from the perspective of their assigned roles. However, the students did not clarify whether they learned more through this SSI-based classroom instruction than through conventional science teaching approaches.